Excitation Cross Section of Argon by Positon Impact at 14.0eV - S. Saxena, K. Kumar* and (Journal of Experimental Sciences, 2010)
We have computed excitation cross section (ECS) of Argon by positron impact using time dependent close coupling method at low energy range i.e. 14.0eV. High quality Hartree - Fock Slater orbitals are used to model the target wave function. We have computed the excitation results for noble gases (Ne, Ar, Kr and Xe), but here we are presenting only for Argon atom. Full orthogonalization significantly improves agreement with experimental data for the noble gas series. We have compared ECS results with other available theoretical data as well as experimental measurements. Our present results are found in excellent agreement with other calculations. However some discrepancies suggested that more and more theoretical as well as experimental work is required in future.